Personnel preparation - Scruggs, Thomas E., 1948-; Mastropieri, Margo A., 1951- (JAI, 2008)
Advances in knowledge of effective strategies for the treatment of learning and behavioral disabilities are of little use without highly trained and effective personnel to implement these strategies. In this volume, a number of internationally prominent authors discuss a wide range of important issues in the preparation of those personnel. Topics include reflective teaching and collaborative teacher leadership, teacher preparation for behavior management, research on high quality teachers, federal policy and teacher preparation, multimedia components in teacher preparation, cohort programs, teacher quality in high and low poverty school districts, and sense of community in online courses. Additionally, chapters are included that address issues in personnel preparation in specific academic content areas, such as reading, mathematics, science, and social studies. The chapters included in this volume represent a critical component of our understanding of learning and behavioral disabilities, and will be of interest to teachers, administrators, graduate students, researchers, professionals in personnel preparation programs, and individuals interested in public policy.
Keywords: Special education teachers -- Training of.; Teachers -- Training of.; Teaching of specific groups & persons with special educational needs.; Teacher training.; Education -- Special Education -- Learning Disabilities.; Education -- Professional Development.; elektronické knihy; electronic books